Une fois ne compte pas (Vol. 56):Nihilisme et sens dans L'insoutenable légèreté de l'être - Jørn Boisen (Etudes Romanes, 2006)
Nihilism as it was defined by Nietzsche has not ceased to be a challenge for the literature of the 20th century. With significance and originality quite out of the ordinary Milan Kundera has inquired into the existential condition that has arisen from the following fundamental problem: what opportunities are afforded man, when he is engrossed by the feeling that everything is of worth, yet nothing is of any use? Through an analysis of - both in its aesthetic design and in its thematic development - this book offers an attempt at interpreting the meaning of Kundera's question.